Optimal threshold in low-dose CT quantification of emphysema - Cao, Xianxian; Jin, Chenwang; Tan, Tao; Guo, Youmin (European journal of radiology, 2020)
Low–dose CT is now widely used in the screening of lung cancer and the detection of pulmonary nodules. There has also been increasing interest in using Low–dose CT for evaluating emphysema. In conventional dose CT, the threshold of −950HU is a common threshold for density-based emphysema quantification for worldwide population. However, the optimal threshold for assessing emphysema at low-dose CT has not been determined. The purpose of this study is to determine the optimal threshold for low-dose CT quantification of emphysema for Chinese population. In this study, 548 low-dose chest CT examinations acquired from different subjects (119 none, 49 mild, 163 moderate, 152 severe, and 65 very severe obstruction) are collected. At the level of the entire lung and individual lobes, the extent of emphysema was quantified by the percentage of the low attenuation area (LAA%) at a wide range of thresholds from −850HU to −1000HU. Both Pearson and Spearman’s rank correlation coefficients were used to assess the correlations between 1) LAA% and pulmonary functions and 2) LAA% and the five-category classification. The statistical significance of the difference between correlation coefficients were evaluated using Steiger’Z test. LAA% had a good correlation with both pulmonary function (|r| = 0.1–0.600, p < 0.001) and the five-category classification (r = 0.163–0.602, p < 0.001) in both the entire lung and individual lobes under different thresholds. The highest correlation coefficient is obtained at −940HU instead of -950HU. Low-dose CT can be used for quantitative assessment of emphysema, and the threshold of -940HU is a suitable threshold for quantifying emphysema in low-dose CT images for Chinese population.